2020
DOI: 10.13057/biodiv/d211048
|View full text |Cite
|
Sign up to set email alerts
|

Insect diversity in various distances to forest edge in small nature reserve: A case study of Bantarbolang Nature Reserve, Central Java, Indonesia

Abstract: Abstract. Darsono, Riwidiharso E, Santoso S, Sudiana E, Yani E, Nasution EK, Aprilliana H, Chasanah T. 2020. Insect diversity in various distances to forest edge in small nature reserve: A case study of Bantarbolang Nature Reserve, Central Java, Indonesia. Biodiversitas 21: 4821-4828. A nature reserve is a conservation area with the objective of conserving the biodiversity of the flora and fauna within its boundaries. However, many nature reserves are fragmented into small extent and isolated from natural habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…This is in keeping with broader studies of invertebrate biodiversity at edges, that suggest even sharp habitat edges as defined by major changes in soils and plants do not serve as hard edges but broad transition zones for many invertebrate taxa (Dangerfield et al, 2003). Indeed, forest edges in a tropical forest in Indonesia showed higher levels of insect diversity than the forest interior (Darsono et al, 2020). Whether particular fly species are more likely to carry Bcbva is unclear, but the variation in fly species community composition might be linked to the variation in Bcbva detection rates across habitats.…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with broader studies of invertebrate biodiversity at edges, that suggest even sharp habitat edges as defined by major changes in soils and plants do not serve as hard edges but broad transition zones for many invertebrate taxa (Dangerfield et al, 2003). Indeed, forest edges in a tropical forest in Indonesia showed higher levels of insect diversity than the forest interior (Darsono et al, 2020). Whether particular fly species are more likely to carry Bcbva is unclear, but the variation in fly species community composition might be linked to the variation in Bcbva detection rates across habitats.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the nest predation rate of Magpie Robins seemed to be lower than that of Shamas (3.23% vs. 16%), the difference was not statistically significant. Shamas exhibit a preference for nesting at the forest edges, possibly owing to the relatively higher abundance of insects in that habitat [68,69]. In a study on Blue Tits (Cyanistes caeruleus), supplemental food provisioning could reduce their nest-building times [70].…”
Section: Discussionmentioning
confidence: 99%
“…Other multi‐species studies in Southeast Asia have found that, where hunting is minimal, moderate levels of forest disturbance do not have a strong negative impact on mammal richness and abundance (Tilker et al, 2019; Wearn et al, 2017). The preference for intact forest close to grasslands may be due to the combination of resources valuable to generalist species: early successional fruiting trees, prey densities, and higher quality forage within grasslands (Darsono et al, 2020; Nakashima et al, 2013; Wirth et al, 2008) and refuge from predators and hunters and larger trees for denning within intact forests. In more interior areas of the park, where the risks associated with edges and open habitat are minimal, disturbed forest may provide alternative access to such early successional resources.…”
Section: Discussionmentioning
confidence: 99%